Neonatal exposure to MK‐801 reduces mRNA expression of mGlu3 receptors in the medial prefrontal cortex of adolescent rats. Issue 5 (19th February 2014) - Uehara, Takashi; Sumiyoshi, Tomiki; Rujescu, Dan; Genius, Just; Matsuoka, Tadasu; Takasaki, Ichiro; Itoh, Hiroko; Kurachi, Masayoshi
ABSTRACT Schizophrenia is considered as a "neurodegenerative" and "neurodevelopmental" disorder, the pathophysiology of which may include hypofunction of the N‐methyl‐d‐aspartate receptor (NMDA‐R) or subsequent pathways. Accordingly, administration of NMDA‐R antagonists to rodents during the perinatal period may emulate some core pathophysiological aspects of schizophrenia. The effect of 4‐day (postnatal day; PD 7–10) administration of MK‐801, a selective NMDA‐R antagonist, on gene expression in the medial prefrontal cortex (mPFC), hippocampus, and amygdala was evaluated using quantitative polymerase chain reaction methods. Specifically, we sought to determine whether genes related to Glu transmissions, for example those encoding for NMDA‐Rs, metabotropic Glu receptors (mGluRs), or Glu transporters, were altered by neonatal treatment with MK‐801. Model rats showed downregulation of the mGluR3 subtype in the mPFC around puberty, especially at PD 35 in response to MK‐801 or during ontogenesis without pharmacological manipulations. Genes encoding for other mGluRs subtypes, that is NMDA‐Rs and Glu transporters, were not affected by the neonatal insult. These results suggest that NMDA‐R antagonism in the early course of development modulates the expression of mGluR3 in mPFC around puberty. Thus, mGluR3 may serve as a potential target to prevent the onset and progression of schizophrenia. Synapse 68:202–208, 2014. © 2014 Wiley Periodicals, Inc.